Choosing between Enoxaparin and Fondaparinux for the management of patients with acute coronary syndrome: A systematic review and meta-analysis - Pravesh Kumar Bundhun; Musaben Shaik; Jun Yuan (BMC Cardiovascular Disorders, 2017)
Abstract Background Enoxaparin and Fondaparinux are potential anticoagulants which are used peri-operatively in the management of patients with Acute Coronary Syndrome (ACS). We aimed to compare the adverse clinical outcomes which are associated with the use of these anticoagulants in patients who were treated for ACS. Methods Online databases (PubMed/Medline, EMBASE, Cochrane library) were searched for studies which compared differences in clinical outcomes observed with the use of enoxaparin and fondaparinux in patients who were treated peri-operatively for ACS. Statistical analysis was carried out by Revman 5.3 software with odds ratio (OR) and 95% confidence intervals (CI) as the analytical parameters. Results Seven studies with a total number of 9618 patients (mainly composed of non-ST elevated myocardial infarction/NSTEMI) were included. This analysis showed mortality to be similarly observed between enoxaparin and fondaparinux with OR: 1.05, 95% CI: 0.67–1.63; P = 0.84. Myocardial infarction (MI) and stroke were also not significantly different throughout different follow up periods. However, minor, major and total bleeding were significantly lower with fondaparinux (OR: 0.40, 95% CI: 0.27–0.58; P = 0.00001), (OR: 0.46, 95% CI: 0.32–0.66; P = 0.0001) and (OR: 0.47, 95% CI: 0.37–0.60; P = 0.00001) respectively during the 10-day follow up period. Even during a follow up period of 30 days or a midterm follow up, major and minor bleeding still significantly favored fondaparinux in comparison to enoxaparin. Conclusion In patients who were treated for ACS, fondaparinux might be a better choice when compared to enoxaparin in terms of short to midterm bleeding events. This result was mainly applicable to patients with NSTEMI. However, due to a limited number of patients analyzed, further larger randomized trials should be able to confirm this hypothesis.